Comparative study of variation of ground level ozone concentrations and total column ozone concentrations over Klang Valley. Issue 1 (August 2021) - Azmi, N A; Awang, N R; Ya'Acob, S H
Abstract: Ozone is a gas that plays important role in balancing the Earth's atmosphere thermal and chemical. Ozone is capable of absorbing the harmful sun's ultraviolet (UV) radiation. The stratospheric ozone has protecting humans and the ecosystems on Earth from solar radiation. However, ground level ozone (GLO) has been related to secondary pollutants and greenhouse gases that give adverse impacts on human health and crop yield. Hence, determining ozone concentration measurement is important for air quality status for the environmental and public health warnings. Variations of ground level ozone (GLO) and total column ozone (TCO) concentrations over Klang Valley, Malaysia in 2014 and 2015 were determined in this study. The GLO measurement data was acquired from Department of Environment (DOE) Malaysia and is measured using standard method instrument, UV Absorption Ozone Analyzer Model 400A while, TCO measurement using Ozone Monitoring Instrument (OMI). The analysis suggests that GLO concentrations in all four stations in Klang Valley exceeded the Malaysia Ambient Air Quality Standard (NMAAQS) 2020 prescribed limit of 90 ppb per hour. In both 2014 and 2015, TCO concentration observed higher from May to August with the highest concentration of 290 DU and lowest from November to February with the lowest concentration of 230 DU, suggesting that there is seasonal fluctuation caused by Northeast Monsoon (NEM) and Southwest Monsoon (SWM). This is due to environmental factors during SWM that favour a rise in TCO concentration, such as low precipitation, low relative humidity, high temperature, and prolonged sunshine hours. On the other hand, NEM results in lower TCO concentration due to high precipitation, high relative humidity, cold temperature, and short sunshine hours. Meanwhile, GLO peaks are usually seen towards the end of March through April and in October, according to GLO trend research (40 to 50 ppb). This is during the transitional monsoon season, where the west part of Peninsular Malaysia received precipitation lower than usual.